Optimization of inducers on expression of recombinant chitinase in Escherichia coli using response surface methodology - Norheziwan, Hamsah (2009)
The function of chitinase as a chitin digestive enzyme has attracted the attention as one of the potential materials for control of phytopathogenic fungi and insect pests. However, chitinase is uneconomic for commercialized due to the high cost in its production. The development in recombinant DNA technology has helped to reduce chitinase production cost and enhance its production. The aim of this study is to determine the optimum conditions toward the production of recombinant chitinase in Escherichia coli by manipulating the concentration of inducers (IPTG and lactose). The best concentration of IPTG and lactose as inducers were determined by using the conventional method. Results from conventional method were used for further improvement of optimization by using Response Surface Methodology (RSM). In Response Surface Methodology, the optimization of expression was carried out based on the Central Composite Design (CCD). The effect of the inducers concentration toward the expression level of the recombinant chitinase production were analyzed and optimum values of tested variables for the production of chitinase were 1.19 mM IPTG and 0.98% lactose. Response surface analysis revealed that 0.513 U/ml of chitinase activity was achieved by using the optimized condition. This improved about 13.2-fold compare to initial experiment which produced 0.039 U/ml. This showed that combination between IPTG and lactose has increased the production of recombinant chitinase.